2011
DOI: 10.1002/smj.944
|View full text |Cite
|
Sign up to set email alerts
|

The differing effects of agent and founder CEOs on the firm's market expansion

Abstract: This paper builds and tests the thesis that CEO influence evolves differently for founders and agents. We theorize that at the beginning of their tenures, founder CEOs can pursue market expansion more aggressively than agent CEOs, because they take office with the combination of motivation, power, and requisite knowledge that agent CEOs build over time. Subsequently, however, founder CEOs have less access to the administrative infrastructure necessary to sustain a growing firm, making them less able than agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 67 publications
2
84
0
Order By: Relevance
“…In a study of 173 cable operators, Souder et al (2012) found that founder CEOs were less likely to continue market expansion during their midtenure and their strategic decisions were more severely constrained by market complexity. In terms of firm performance, by studying 94 U.S. public firms, Jayaraman et al (2000) found that founder CEOs led smaller and younger firms to better performance than agent CEOs were able to.…”
Section: Founder Ceos and Firm Risk Takingmentioning
confidence: 98%
“…In a study of 173 cable operators, Souder et al (2012) found that founder CEOs were less likely to continue market expansion during their midtenure and their strategic decisions were more severely constrained by market complexity. In terms of firm performance, by studying 94 U.S. public firms, Jayaraman et al (2000) found that founder CEOs led smaller and younger firms to better performance than agent CEOs were able to.…”
Section: Founder Ceos and Firm Risk Takingmentioning
confidence: 98%
“…This risk aversion causes CEOs to surrender to the status quo (Hambrick, 2007) and further pushes longer-tenure CEOs away from the external market environment (Luo et al, 2014). When an SME goes international, it has little international exposure, so it is important to undertake major strategic change in the process of internationalization (Souder, Simsek, & Johnson, 2012) by absorbing fresh ideas, enhancing their information base, and making bold decisions. Longer-tenure CEOs' decision-making relies less on matching internal capacities and external opportunities and more on their own existing knowledge and past experiences, which may be a poor fit for successful internationalization (Hambrick & Fukutomi, 1991;Miller, 1991).…”
Section: Ceo Tenurementioning
confidence: 99%
“…Such research has largely been at a senior level: it has attempted to separate CEO effects from industry or firm effects in order to calculate the explanatory power of leaders and their characteristics (e.g. Thomas 1988;Finkelstein & Hambrick, 1996;Waldman & Yammarino 1999;Souder, Simsek & Johnson, 2012;Dezso & Ross, 2012;Bloom et al 2012). There is a literature on high-involvement management (Guthrie 2001, Bryson et al 2005, Bockerman et al 2012, Boxall & Macky 2014, but that has not tackled the exact issue considered in this paper, and on the influence of private equity (Agrawal & Tambe 2014).…”
Section:  Whether the Supervisor Could In An Emergency Do The Employmentioning
confidence: 99%